FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK (STUDI EMPIRIS DI KPP PRATAMA KARANGANYAR) - Murni Sulistyowati; Basuki Sri Rahayu (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze the effect of Tax Paying Awareness, Tax Sanctions, Fiscal Service Quality, and Knowledge and Understanding of Tax Regulations on Taxpayer Compliance at Karanganyar Pratama Tax Office. The population of this study is all registered individual taxpayers in the Pratama Karanganyar Tax Office in 2017, amounting to 82,318. The sampling technique uses Simple Random Sampling technique with a total sample of 100 respondents. The analysis technique consisted of Validity Test, Reliability Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Normality Test, Multiple Linear Analysis, T Test, F Test, and Determination Test. The Hypothesis Test Results prove that: 1) Tax Paying Awareness has a positive and significant effect on Taxpayer Compliance. 2) Tax Sanctions have a positive and significant effect on Taxpayer Compliance. 3) Fiscal Service Quality has a positive and significant effect on Taxpayer Compliance. 4) Knowledge and Understanding of Tax Regulations has a positive and significant effect on Taxpayer Compliance. 5) Tax Paying Awareness, Tax Sanctions, Fiscal Service Quality, and Knowledge and Understanding of Tax Regulations together have a significant effect on Taxpayer Compliance.